The use of e-wallet in the era of globalization / Norliana Abdullah … [et al.] - Abdullah, Norliana; Mohd Azhari, Izzati Aina; Abdul Aziz, Nurul Alwani; Mohd Fadzil, Intan Batrisya; Nazri, Muhammad Hafizuddin (2023)
Financial technology has become one of the most important aspects of the financial services industry. One of the most prominent financial technologies in Malaysia is the e-wallet. Because of this, understand the factors, which influence the user, intention to use and user satisfaction with the use of e-wallet is important. E-wallet provides convenience for users to make purchases. The results correlate with expectancy theory, which suggests that confirmation of consumer expectations will lead to consumer satisfaction. E-wallets, also known as digital wallets or mobile wallets, are software applications that allow users to store and manage their financial assets electronically. They provide a digital version of the traditional wallet, allowing users to carry out financial transactions online or via a mobile device. E-wallets work by linking a user's bank account, credit card, or debit card to the e-wallet account. Once linked, users can use the e-wallet to perform various financial transactions such as money transfers, bill payments, online purchases, and mobile recharges, among others. E-wallets offer several advantages over traditional payment methods. They provide a more streamlined and secure way to manage finances, especially for online transactions. With e-wallets, users can avoid the need to carry physical cash or cards, reducing the risk of loss or theft. E-wallets also offer additional features such as cashback rewards, loyalty programs, and digital receipts, making them a popular choice for many users. They are widely used for online shopping, paying bills, booking travel, and sending money to friends and family. Overall, e-wallets have revolutionized the way people manage their finances, providing a more convenient and secure way to make transactions in the digital age.